Stability analysis of neutral systems with mixed interval time-varying delays and nonlinear disturbances. Issue 6 (April 2020) - Chen, Wenbin; Xu, Shengyuan; Li, Yongmin; Zhang, Zhengqiang
Abstract: This paper studies the problem of stability analysis for neutral systems with mixed time-varying delays and nonlinear disturbances. Improved stability criteria are obtained by applying augmented Lyapunov-Krasovskii methodology. First, a novel Lyapunov–Krasovskii functional containing the intersection relationship terms about mixed time-varying delays and their upper-lower bounds with lower bounds limited to be strictly greater than zero is fully established. Second, the upper bounds for integral terms presented are accurately estimated based on integral intervals decomposition approach. Third, a less conservative stability condition in terms of linear matrix inequality is derived by utilizing a new quadratic inequality technology. In the end, two numerical examples are given to illustrate the effectiveness and the advantages of the proposed method.